Targeting the tumor microenvironment with anti-neu/anti-CD40 conjugated nanoparticles for the induction of antitumor immune responses - Dominguez, Ana Lucia (2009)
Clinical and preclinical data indicate that immunotherapeutic interventions could induce immune responses capable of controlling or retard the tumor growth. However, immunotherapies need to be further optimized. We hypothesized that a more effective strategy for tumor eradication is to directly target the tumor microenvironment in order to generate a proinflammatory response and induce a localized antitumor immune response capable of eliminating the tumor cells. Nanoparticles have been proven to be an effective delivery system. In these studies we evaluated conjugated anti-RNEU and anti-CD40 antibodies onto PLA-(poly DL-lactic acid)-biodegradable nanoparticles (PLA-NP) for the induction of antitumor immune responses. The anti-neu/anti-CD40-NP were functional in vitro recognizing RNEU(+) tumors and activating dendritic cells. The delivery of anti-neu/anti-CD40-NP but not anti-neu-NP or anti-CD40-NP induced an antitumor response resulting in complete tumor elimination and generation of protective memory responses. The anti-neu/anti-CD40-NP specifically activated an antitumor response against RNEU(+) tumors but not against RNEU(−) tumors. The antitumor immune responses correlate with the induction of a Th1 proinflammatory response, reduction in the number of Tregs within the tumor and activation of a specific cytotoxic response. These results indicate that anti-neu/anti-CD40-NP with immunomodulatory properties are safe and can be used effectively as cancer vaccines strategy for the specific induction of antitumor immune responses.